ロケット ニヨ ル オーロラ カンソク Xセン カンソク - 小玉, 正弘; コダマ, マサヒロ; KODAMA, Masahiro (国立極地研究所, 1975)
P(論文) 1971～73年にかけて,昭和基地で行われたロケット実験で得られたオーロラX線の観測結果について概報する.観測は前後6回行われ.Nalシンチレーション・カウンターを使用,4 keV以上のオーロラX線フラックスを観測した.その結果,X線の空間強度分布が予想以上に早く時間変化し.また,それが,オーロラ可視光,紫外光放射の変化と良相関を有することがわかった. This report briefly summarizes preliminary results of a series of rocket experiments on auroral X-rays carried out at Syowa Station, Antarctica during 1971-1973. Dual sets of sounding rockets were launched each year to an altitude between 100 km and 130 km. From five of six nights in total, distinct auroral X-ray fluxes with energies above 4 keV were recorded using one or two Nal scintillation counters. These recordings revealed the existence of a rapid time variation of the spatial distribution, a good relation with visible and ultraviolet emissions, and a spectral change with time of the auroral X-rays. departmental bulletin paper